DESAIN PERANGKAT PEMBELAJARAN BLENDED LEARNING BERBASIS EDMODO PADA MATERI HIDROKARBON DAN MINYAK BUMI - Murni Murni Murni (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
AbstractThe blandes learning model has not yet been implemented so that it needed for new innovations in learning. Hydrocarbon and Crude Oil Lessons were abstract and compact lessons, so it needed time to finish it. This research aimed at producing Edmodo based blended learning media on Hydrocarbon and Crude Oil lessons and knowing the validity level of the produced media. It was Research and Development (R&D) with Borg & Gall model. The subjects of this research were Chemistry lecturers and teachers. Techniques of collecting the data were interview, validity test questionnaire, practicality test, and documentation. Analyzing the data was done by using qualitative and quantitative descriptive analysis techniques. The research findings showed that it was obtained 84.6% (very valid) for validity level of learning implementation plan, 84.4% (very valid) for validity level of student workbook, and 80.4% (valid), 83.4%( very practice) for practicality level of learning implementation plan, and 82.9% (very practice) for practicality level of student workbook, and 80.4% (practice) for practicality level of Edmodo e-learning media. Based on this research, it could be concluded that Edmodo based blended learning media on Hydrocarbon and Crude Oil lessons could be tested. Keywords: Learning Media, Edmodo, Hydrocarbon and Crude Oil